Perbedaan Pengaruh Metode Mengajar dan Kemampuan Gerak Terhadap Keterampilan Teknik Dasar Bermain Bola Voli (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2008)
This watchfulness aim (1) to detects method influence difference teaches resiprokal and self check (investigate self) towards technique know-how base play bolavoli student, (2) to detect tall movement ability influence difference and low towards technique know-how base play Volley Ball, (3) detect interaction between method teaches and movement ability in influence result learns technique know-how base play volley ball. Watchfulness is carried out with experiment method with factorial design 2x2. This watchfulness sample class son student VIII MTSN 2 fields, as much as 40 students. Sample is divided in 4 (four) experiment groups that is 1) experiment group 1 (n-10) with method resi-prokal that has tall movement ability, 2) experiment group 2 (n-10) with method resiprokal that has low movement ability, 3) experiment group 3 (n-10) with method self check that has tall movement ability, 4) experiment group 4 (n-10) with method self check that has low movement ability. Data got from technique know-how test base play volley ball, use instrument aahper volleyball skill test manual that consist of test passing and test servis under. data analysis technique by using analysis varians anava 2 x 2 with standard significant? = 0,05. Watchfulness result see that: 1) there difference significant between method teaches resiprokal and method teaches self check towards technique know-how base play volley ball, where does method teach resiprokal has result higher than method result self check because fcount = 8,41 > ftable = 4,11.2) there difference significant between tall movement ability and low movement ability towards technique know-how base plays volley ball, where is student ably tall movement has higher result than low movement ability result because fcount = 6,78 > ftable = 4,11.3) there inter-action between method teaches and movement ability towards technique know-how base play volley ball this matter is showed by fcount = 13,90 > ftable = 4,11. Based on ave-rage result () every group, will show that student that has tall movement ability more will fit given study with method resiprokal,Â  and student that has low movement ability more will fit given study with method self check.Keywords: Method Teaches, Movement Ability, Technique Base Volley Ball